The cyclicality of government expenditure in developing country: the case of Indonesia - Haryo Kuncoro (Economic Journal of Emerging Markets, 2014)
This paper analyzes the cyclicality and the relationship between government expenditure and output of Indonesia, 1999-2012 using Johansen co-integration test and the error correction model. The results confirm that in the short-run the government expenditure reveals counter-cyclical but pro-cyclical in the longrun. Output and government expenditure are co-integrated and it implies the existence of long-term relationship. The value of short-run elasticity coefficient for government expenditure is relatively high. In contrast, the long-run elasticity coefficient is lower and statistically greater than unity confirming the voracity hypothesis. Furthermore, there is no significant difference of government spending in good and bad times.